Utilization of Spent Tea Waste for the Development of New Milk Chocolate Product - Raza, Rashid; Ajaz, Aqsa; Rashid, Misha; Nasir, Aqsa (Journal of Research (Science), 2025)
Utilization of waste has become the prime importance and a great challenge in food processing. Black tea is normally high in consumption in Pakistan and the tea waste is generally discarded or used as fertilizer. Dried spent tea waste can be used as a replacer to cocoa powder for the production of various chocolate products. In the current study milk chocolate samples were prepared using five various compositions i.e. 1, 3, 5, 7 and 9g/100g of spent tea waste replacing cocoa powder along-with constant amount of other ingredients. Among the various combinations, the newly developed milk chocolate sample containing tea waste in a ratio of 5g/100g was found to be better for its functional properties and sensory evaluation. The water activity, pH, hardness, moisture, ash, protein, fat, fiber, carbohydrate, and energy content of newly developed samples were found to be 0.50Aw, 6.54, 4.54N, 6.9%, 0.743%, 7.35%, 20.8%, 2.60%, 26.4% and 510kcal/100g. The newly developed milk chocolate was wrapped in metallic coated polythene wrapper, packed in 50-micron polythene bags and stored at ambient (25 ± 2oC) as well as refrigerated (5 ± 2oC) condition for 6 months. The storage studies of new product indicated that the TSS, reducing and total sugars increased with the advancement of storage period, while moisture and acidity content decreased. The rate of both reactions during storage was observed relatively higher at ambient temperature than refrigerated temperature. Formation of bloom on the sample during storage at ambient temperature 25 ± 2°C and refrigerated temperature 5 ± 2°C, was also determined using standard method. By the end of 6 weeks no bloom formation was observed but after 8-week bloom formation was started to be detected. The similar composition of tea waste and cocoa powder make it possible to be used instead of cocoa powder. It is therefore, concluded that tea waste is a better substitute of a cocoa powder with an affordable initial cost and it can be used in a preparation of various chocolate products.